2020
DOI: 10.3389/fped.2020.00350
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Corticosteroid Therapy in Children Undergoing Cardiac Surgery: A Systematic Review and Meta-Analysis

Abstract: Background: The benefit-risk profile of perioperative corticosteroids in pediatric patients undergoing cardiac surgery remains controversial. Objective: To investigate the influence of perioperative corticosteroids on the postoperative mortality and clinical outcomes in pediatric patients undergoing cardiac surgery with cardiopulmonary bypass. Methods: We conducted a systematic search using MEDLINE, EMBASE, and Cochrane Database through August 31, 2019. We included randomized controlled trials comparing periop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Factually, corticosteroids have been both the most effective and most controversial therapeutic medications for preventing the SIRS associated with CPB. The above‐mentioned pathophysiologic processes as a result of CPB were, however, substantially relieved by the development of perfusion and postoperative treatment regimens, leading to a decrease in mortality and morbidity 39,40 . Hence, it was not known if or to what degree corticosteroids' direct inhibition of SIRS would lead to better clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Factually, corticosteroids have been both the most effective and most controversial therapeutic medications for preventing the SIRS associated with CPB. The above‐mentioned pathophysiologic processes as a result of CPB were, however, substantially relieved by the development of perfusion and postoperative treatment regimens, leading to a decrease in mortality and morbidity 39,40 . Hence, it was not known if or to what degree corticosteroids' direct inhibition of SIRS would lead to better clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid therapy was associated with increased blood glucose concentrations on postoperative day 1 and a higher risk of postoperative use of insulin. The inotrope score on postoperative day 1 was reduced ( 26 ).…”
Section: Corticosteroids In Pediatric Cardiac Surgery Patientsmentioning
confidence: 99%
“…The authors state that they cannot provide implications for clinical practice and highlight that adequately performed and well-conducted randomized trials are necessary, powered for outcome variables, and not inflammatory mediators ( 25 ). Another recently performed meta-analysis included 17 studies ( 26 ). The authors found no differences in mortality, DMV, incidence of LCOS, infection, AKI, and LOS in the ICU.…”
Section: Corticosteroids In Pediatric Cardiac Surgery Patientsmentioning
confidence: 99%
“…Hence, anti-inflammatory therapy with corticosteroids has been extensively studied for those undergoing cardiac surgery requiring CPB [33,34] . In addition, several studies have investigated the cellular mechanisms whereby corticosteroid supplementation may be beneficial [34,35] . However, a recent meta-analysis of 17 RCTs and 848 pediatric patients by Li et al [36] in 2020 concluded that children receiving corticosteroids did not have a reduction in all-cause mortality compared to controls.…”
Section: Corticosteroidsmentioning
confidence: 99%